Global Infectious Diseases in January 2023: Monthly Analysis - Minjing He; Shuqiong Zhang; Qun Su; Dongliang Liu; Guodan Li; Qi Xiang; Yinfu Sun; Yi Luo; Taihan Li; Yufan Wu; Jiazhen Zou; Shiping He; et al. (Zoonoses, 2023)
Infectious diseases are a major threat to global health and the economic stability of societies worldwide. To prevent outbreaks, monitoring the growth trends of infectious diseases appears to be particularly important and necessary. Herein, data from epidemiological websites, such as the World Health Organization and National Health Council are used to illustrate the outbreak trends for infectious diseases worldwide. In the context of the COVID-19 pandemic, a global resurgence in other infectious diseases has been observed, particularly influenza in the United States. Proper surveillance and effective strategies are urgently required to keep emerging infectious diseases under control.